2003
DOI: 10.1210/jc.2002-021548
|View full text |Cite
|
Sign up to set email alerts
|

Bone Histomorphometry in Children and Adolescents with β-Thalassemia Disease: Iron-Associated Focal Osteomalacia

Abstract: Thalassemia/hemoglobinopathy is a hereditary disease that causes chronic anemia and increased erythropoiesis. Consequently, an expansion of bone marrow spaces may contribute to osteopenia/osteoporosis. However, the pathogenesis of bone changes is not yet known. We, therefore, carried out the study on bone histomorphometry and biochemical and hormonal profiles in children and adolescents with suboptimally treated beta-thalassemia disease with the hope of gaining some new insight into the cellular and structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
127
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 27 publications
9
127
1
3
Order By: Relevance
“…In addition, iron deposits appeared along mineralization fronts and osteoid surfaces, whereas focal thickened osteoid seams were found together with focal iron deposits (33,43). Finally, dynamic bone formation histomorphometry studies established reduced bone formation rate in TM patients (33). This reduced bone formation is thought to-date to be mainly the result of iron poisoning in osteoblasts and/or the result of reduced function of GH and IGF-1 axis in TM patients.…”
Section: Acquired Factorsmentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, iron deposits appeared along mineralization fronts and osteoid surfaces, whereas focal thickened osteoid seams were found together with focal iron deposits (33,43). Finally, dynamic bone formation histomorphometry studies established reduced bone formation rate in TM patients (33). This reduced bone formation is thought to-date to be mainly the result of iron poisoning in osteoblasts and/or the result of reduced function of GH and IGF-1 axis in TM patients.…”
Section: Acquired Factorsmentioning
confidence: 92%
“…Iron deposition in the bone impairs osteoid maturation and inhibits mineralization locally, resulting in focal osteomalakia. The mechanism by which iron overload interferes in osteoid maturation and mineralization includes the incorporation of iron into crystals of calcium hydroxyapatite, which consequently affects the growth of hydroxyapatite crystals and reduces the bone metabolism unit tensile strength (33). Furthermore, desferrioxamine inhibits DNA synthesis, osteoblast, and fibroblast proliferation, osteoblast precursors differentiation, and collagen formation, although enhances osteoblast apoptosis, especially in patients who receive inappropriately high doses of desferrioxamine (34).…”
Section: Acquired Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis of thalassemia-induced bone disease is multifactorial and includes bone marrow expansion, endocrine dysfunction, and iron overload, as well as genetic susceptibility to attainment of low peak bone mass (17,18). At tissue level, it has been demonstrated that there is an osteoblast dysfunction together with increased osteoclast activity leading to imbalanced bone turnover in favor of bone resorption (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%